MANAJEMEN SUMBER DAYA MANUSIA PENDIDIK DAN TENAGA KEPEN-DIDIKAN SD MUHAMMADIYAH 2 BOJONEGORO DALAM PENERAPAN KU-RIKULUM MERDEKA - Nurwanda Widiya Prasiska; Yuni Asih; Cebeng Alhudayatul Ustadza; Siti Inganah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the human resource management of educators and education personnel at Muhammadiyah 2 Elementary School in Bojonegoro in implementing the Independent Curriculum. This study used a descriptive qualitative approach. The research subjects consisted of the principal, teachers, school operators, and administrative staff. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that the management of educators and education personnel has been implemented through a process of planning, organizing, implementing, monitoring, and periodic evaluation. The implementation of the Independent Curriculum is supported by teacher training programs, learning communities, workshops, and the use of the Independent Teaching Platform (PMM). However, several obstacles remain, such as changes in teacher mindsets, time constraints in developing open modules and P5 projects, and teachers' technological skills. Therefore, sustainable human resource development and collaborative support are needed to optimize the implementation of the Independent Curriculum in elementary schools.